THE CURRENT STATE OF FORMATION OF FINANCIAL CENTERS IN THE COUNTRIES OF CENTRAL ASIA (ON THE EXAMPLE OF THE FINANCIAL CENTER OF THE CITY OF ASTANA) - Akhmadalieva Nikholakhon (Scholar Express Journals, 2021)
The article analyzes the current position of international financial centers (IFC) in Central Asia as one of the essential institutions and factors for financial globalization. Risks of functioning of IFC, their classifications and meaning. The article also highlights current position of the International Financial Center Astana, its role in improving country’s financial and economic potential and its global competitiveness.
Keywords: International financial centers; monetary obligation; currency regulation; Center